Tadbir Urus Dalam Gerakan Koperasi: Penilaian Tahap Pematuhan Dan Prestasi Kewangan Koperasi - Rasimah Aripin; Hassan Hj Ahmad; Nasibah Ahmad; Norbiha Kasmuri; Noraesyah Saari (Maktab Kerjasama Malaysia, 2024)
Tiada abstrak